Band and Loop Space Maintainer Among Children Between the Age Group Of 6-10 Years - A Retrospective Study - CHRISTOPHER, VARUSHA SHARON; JEEVANANDAN, GANESH; RANJAN, MANISH (The journal of contemporary issues in business and government, 2021)
Premature loss of teeth in children leads to space loss and affects arch integrity. Space maintainer and space maintenance is an important part of paediatric dentistry as well as a part of interceptive orthodontics. This study aims to determine the prevalence of band and loop space maintainers among children who are 6-10 years old. Data collection was done from going through 86,000 patient records from June 2019 to April 2020. Total sample size was 44 children who were inserted with a band and loop space maintainer. Chi- square test is done to analyse the significance of the study. The analysis showed that the band and loop space maintainer are more prevalent in 6 year old children and mostly done in female children. The reason for tooth loss was due to extensive caries. However, the study showed positive correlation but there was no significance since p=0.276. Use of space maintainers is an important step in interceptive orthodontics and the study concluded that it is more prevalent in 6 year old children.